Penerapan Evidence Based Kompres Air Hangat pada Gastritis - Kairupan, Michelle; Lumape, Yudith Tania (Yayasan Syalom Cipta Sumikolah, 2025)
Warm compress action can increase blood flow to the injured body part, then increase the delivery of leukocytes and antibiotics to the injured area, increase muscle relaxation and reduce pain due to spasms or stiffness, in addition it can also increase blood flow and increase the movement of waste and nutrients. At that time the blood vessels will widen so as to improve blood circulation in the tissue. The aim is to determine the effectiveness of the implementation of warm compresses on abdominal pain in gastritis patients. The method used is a case study. The subjects used were gastritis patients with abdominal pain problems at the Panti Werdha Damai Ranomuut. The results of the study with the application of evidence-based nursing warm water compress therapy carried out for 3 days, found the level of pain on the first day was on a pain scale of 7, and on the third day decreased to a scale of 0, from the results of the evaluation it was found that warm water compress therapy was effective in reducing pain levels. The conclusion of the case study results showed that the level of pain after being given warm water compress therapy intervention there was a decrease in the level of pain. Suggestions to all health workers to be able to provide non-pharmacological therapy in the form of warm water compress therapy and provide education to clients so that they can apply this therapy when they feel pain due to gastritis.